A New Method for Plane Equilibrium Injection-production Adjustment of Water-drive Reservoir. (June 2020) - Sun, Guangyi; Liu, Yingxian; Chang, Huijiang; Chen, Xiaoming; Dong, Chi
Abstract: In view of the lack of theoretical research on plane equilibrium injection-production adjustment in water drive reservoir, the production prediction method under the condition of variable pressure difference of production well is deduced according to Buckley Leverett non-piston displacement theory. Taking the same degree of extraction as the goal, the adjustment method of plane equilibrium injection-production per unit time is put forward. The evaluation coefficient of the optimal equilibrium injection-production scheme is defined, which can guide the optimization of the equilibrium injection-production scheme. Through theoretical model analysis, it is considered that the adjustment method of plane equilibrium injection-production is reasonable and reliable. Seven kinds of adjustment schemes are designed for BZ oilfield in Bohai Sea. Of equilibrium displacement time. When the equilibrium displacement time is more than 10 years, the increment of recovery degree slows down to about 1.8%. Equilibrium injection-production adjustment was carried out for 1195 sand body in BZ oilfield. The sand body increased oil by 25m3/d per day, and the natural decline rate decreased by 1.1%.